Application of the Averaging Method to the Optimal Control of Parabolic Differential Inclusions on the Semi-Axis - Nina Kasimova; Petro Feketa (Axioms)
In this paper, we use the averaging method to find an approximate solution for the optimal control of parabolic differential inclusion with fast-oscillating coefficients on a semi-axis.